Engineered Spider Silk Proteins for Biomimetic Spinning of Fibers with Toughness Equal to Dragline Silks. (25th March 2022) - Arndt, Tina; Greco, Gabriele; Schmuck, Benjamin; Bunz, Jessica; Shilkova, Olga; Francis, Juanita; Pugno, Nicola M; Jaudzems, Kristaps; Barth, Andreas; Johansson, Jan; Rising, Anna
Abstract: Spider silk is the toughest fiber found in nature, and bulk production of artificial spider silk that matches its mechanical properties remains elusive. Development of miniature spider silk proteins (mini‐spidroins) has made large‐scale fiber production economically feasible, but the fibers' mechanical properties are inferior to native silk. The spider silk fiber's tensile strength is conferred by poly‐alanine stretches that are zipped together by tight side chain packing in β‐sheet crystals. Spidroins are secreted so they must be void of long stretches of hydrophobic residues, since such segments get inserted into the endoplasmic reticulum membrane. At the same time, hydrophobic residues have high β‐strand propensity and can mediate tight inter‐β‐sheet interactions, features that are attractive for generation of strong artificial silks. Protein production in prokaryotes can circumvent biological laws that spiders, being eukaryotic organisms, must obey, and the authors thus design mini‐spidroins that are predicted to more avidly form stronger β‐sheets than the wildtype protein. Biomimetic spinning of the engineered mini‐spidroins indeed results in fibers with increased tensile strength and two fiber types display toughness equal to native dragline silks. Bioreactor expression and purification result in a protein yield of ≈9 g L −1 which is in line with requirements for economically feasible bulk scale production. Abstract : Basic biological insights and rational protein engineering is used to design engineered spider silk proteins which are spun into fibers in a biomimetic spinning set‐up. The fibers show increased tensile strength compared to the original nonengineered fiber, and two of the fiber types display a toughness equal to native dragline silks. The high protein yields allow translation into industrial production.